La duración en el mercado de vivienda nueva en México - Carolina Rodríguez-Zamora; Alejandro Morales Ramírez (Banco de México, 2018)
– In this article we study the market duration of new housing built by developers in Mexico between 2013 and 2015. In particular, this document discusses whether the physical characteristics of housing, state of location, date put on sale, time of construction, the initial price and the size of the developer have any effect on the duration of new houses in the market. We use a survival analysis Cox model. The most important results indicate that the probability of a new house being sold between t and t+1 (hazard rate) decreases with time and, in general, is lower for units of larger size, those that took much time on the construction process, and those constructed by small developers.
Keywords: R21; R31; C41; 330; Duration; housing; time-on-the-market; Mexico